VOLCANIC ACTIVITY IN THE KOŽUF MOUNTAIN AREA AND IMPLICATIONS FOR THE DISTRIBUTION OF RARE EARTH ELEMENTS IN DIATOMITE AND TRIDYMITE (Geologica Macedonica, 2019)
This paper presents the results of an investigation into the distribution of rare earth elements (REEs) in diatomite and tridymite from the Kožuf Mountain volcanic area. The REEs comprise fifteen chemical elements from lanthanum to lutetium (atomic numbers 57–71), characterized by similar chemical properties. In order to study their distribution, samples of the Vitačevo diatomite and Alsar tridymite sediments were taken and analyzed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The chondritic normalization curves show enrichment in light rare earth elements (LREEs), a negative europium (Eu) anomaly in all samples, and a progressive depletion of heavy rare earth elements (HREEs). Two hypotheses are discussed: the nature of the parent rocks of the sediments (volcanic rocks of the Kožuf Mountain) and the physico-chemical conditions of sedimentation, particularly complexation and oxidoreduction phenomena. There is a strong correlation between the distribution of REEs in volcanic rocks and the distribution of REEs in sedimentary diatomite and the acidic volcanics (tridymite). Key words: diatomite; tridymite; rare earth elements; Kožuf Mountain